STUDI KARAKTERISTIK DAN PETROGENESA JASPER DI DESA LIMBASARI DAN SEKITARNYA KECAMATAN BOBOTSARI KABUPATEN PURBALINGGA PROPINSI JAWA TENGAH - , SOKHWATUL AGHNIA ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Jasper is a pure mineral quartz and opaque due to impurities and impregnated by their nature green jasper, red, yellow, or brown jasper and some have more than one color. Material contents jasper is SiO2 of more than 80%. Jasper in Purbalingga is potential, although only local, one of which unfolds in the village Limbasari, District Bobotsari, Purbalingga, Central Java. The purpose of this study was to determine the characteristics and petrogenesa jasper using petrographic analysis and chemical analysis XRF. In the study area there are two morphological units, three are unit slope sloping hills and steep sloping hills unit. Stratigraphy of the study area is divided into 3 lithologies, Three are unit basalt lava, marl, and calcareous sandstone. This jasper include the type of magma differentiation with low temperatures and a vein in basalt lava. Volcanic rocks of the study area derived from basaltic parent magma calc-alkaline rocks which when differentiated produce that contains quartz. Tectonic environment of rock formation in the form of the subduction zone, an area of research is high intensity geological structure. This structure is a factor controlling the movement of hydrothermal solution and fracture filling jasper in basalt lava.